PELAKSANAAN BANTUAN HUKUM TERHADAP KORBAN KEKERASAN DALAM RUMAH TANGGA DI KOTA PEKANBARU - Siregar, Irfan MH; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
In General, the community considers that household violence was a private matter that did not have were interfered by others. But due to the increasing number and is a violation of human rights, household violence must be solved in particular the granting of legal aid for victims of household violence. The purpose of this scription writing: first, the implementation of legal aid to victims of household violence in Pekanbaru City, second, the obstacles encountered in the implementation of legal aid to victims of household violence in Pekanbaru City, thirdly, efforts are being made in overcoming the obstacles in the implementation of legal aid to victims of household violence in Pekanbaru City. This type of research can be classified into types of juridical sociological research. This research was conducted in the Pekanbaru City, while population and sample was a whole party that deals with issues that are examined in this study, the data sources used, the primary data, secondary data, and tertiary data, techniques of collecting data in this study with the depth interviews, observation, and study of librarianship. The analysis of the data used is qualitative data and technique draw conclusions by deductive way. From the results of the research there are three basic issues that can be inferred. First, the implementation of legal aid to victims of household violence in Pekanbaru City has yet to be implemented by Law number 16 of 2011 about legal aid. Second, the obstacles encountered in the implementation of legal aid to victims of household violence in Pekanbaru City that mechanisms of the legal aid administrative documents arrangements tend to be convoluted, legal aid givers apparatus limitations, lack of infrastructure and facilities in the relevant agencies as well as legal assistance covered up to the assistance funds to the institution of legal aid giver, Third, effort to overcoming obstacles in the legal assistance to victims of the household violence in Pekanbaru City namely approach in preventive and approach in curative, advice writer, first, need of special supervision on the implementation of legal assistance, especially legal assistance to victims of the household violence, second, expected the with regulations which regulates coordination between agencies related legal assistance, third, need of commitment serious, quick, and firmly from government to opening access to possible to society and related agencies including providing facilities. Keywords : Legal Aid â Victims - Household Violence